Penerapan Model Pembelajaran Take and Give pada Pelajaran IPA Kelas IV SDN 75 Lubuklinggau - Bella Putri Amelia; Satinem Satinem; Abu Bakar (Journal of Elementary School (JOES), 2022)
ABSTRACT This study aims to determine the completeness of students' science learning outcomes after the Take and Give learning model is applied to the fourth grade of SD Negeri 75 Lubuklinggau. The type of research used is Experiment. The research population is all fourth grade students at SD Negeri 75 Lubuklinggau for the 2021/2022 academic year. Sample selection using saturated sampling technique. The research sample was taken as many as 24 students and taught with Take and Give learning. This research method is a quasi-experimental. The data collection technique used an essay test, then analyzed with the z test. results Based on the research and discussion obtained data with an average of 70.22 with learning completeness (83.33%) the results of the large z analysis zcount = 4.28 > ztable = 1.64 (zcount > ztable) which indicates that Ho is rejected and Ha If it is accepted, it can be said that the science learning outcomes of fourth grade students of SD Negeri 75 Lubuklinggau after the application of the Take and Give learning model are in the complete significant category Keywords: Application, Take and Give, Science Learning Outcomes.